From the Shadow of Overconfidence Into the Light of Humility: Reflections on Experiential Learning Activities Gone Awry. (April 2019) - Edelson, Steven A.; Lo, Kevin D.; Nelson, Terry; Stark, Gary; Stratton, Micheal T.; van Esch, Chantal
Many instructors use experiential learning techniques to link students' academic experience with the reality that awaits them professionally. Careful planning and reflecting on experiential activities usually take place prior to implementation to ensure that prescribed student learning outcomes are met. Hence, management educators' confidence soars when outcomes meet or exceed their expectations, and there is the intrinsic reward of seeing students succeed. Subsequently, effective application of activities can lead to overconfidence in implementing routine as well as new activities. What happens, however, when an activity goes awry? Can it be salvaged? In this article, we explore overconfidence as the shadow that can disrupt a faculty's well-meaning activity, leading to something unexpected with unintended learning consequences for the instructor and students. Then, we analyze several of our activities gone awry as a result of overconfidence. Finally, we suggest humility as a spotlight that can help us move out of the shadow cast by overconfidence, thus helping faculty deal with the dark side of experiential exercises.